E3 ligase SAUL1 serves as a positive regulator of PAMP‐triggered immunity and its homeostasis is monitored by immune receptor SOC3. Issue 4 (10th July 2017) - Tong, Meixuezi; Kotur, Tanja; Liang, Wanwan; Vogelmann, Katja; Kleine, Tatjana; Leister, Dario; Brieske, Catharina; Yang, Shuhua; Lüdke, Daniel; Wiermer, Marcel; Zhang, Yuelin; Li, Xin; et al.
Summary: In both plants and animals, intracellular nucleotide‐binding leucine‐rich repeat proteins (NLRs; or Nod‐like receptors) serve as immune receptors to recognize pathogen‐derived molecules and mount effective immune responses against microbial infections. Plant NLRs often guard the presence or activity of other host proteins, which are the direct virulence targets of pathogen effectors. These guardees are sometimes immune‐promoting components such as those in a mitogen‐activated protein kinase cascade. Plant E3 ligases serve many roles in immune regulation, but it is unclear whether they can also be guarded by NLRs. Here, we report on an immune‐regulating E3 ligase SAUL1, whose homeostasis is monitored by a Toll interleukin 1 receptor (TIR)‐type NLR (TNL), SOC3. SOC3 can associate with SAUL1, and either loss or overexpression of SAUL1 triggers autoimmunity mediated by SOC3. By contrast, SAUL1 functions redundantly with its close homolog PUB43 to promote PAMP‐triggered immunity (PTI). Taken together, the E3 ligase SAUL1 serves as a positive regulator of PTI and its homeostasis is monitored by the TNL SOC3.